Method for purifying phosphogypsum

Through the coupling process of leaching and electrolytics, combined with homemade fluorine removal agent and recycling technology, the problems of poor impurity removal effect and high treatment cost in phosphogypsum are solved, and high purity and high whiteness are achieved, reducing phosphogypsum products. production costs and drug consumption.

CN119430260APending Publication Date: 2025-02-14YIDU XINGFA CHEMICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610398.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing phosphogypsum purification and whitening technology has problems such as poor impurities removal, high treatment cost, and high drug consumption, making it difficult to achieve high purity and high whiteness phosphogypsum products.

Method used

The leaching process is adopted in which the leaching agent and the fluorine-fixed agent is combined, and then the electrolytic reaction is carried out by the double-chamber separator electrolysis method to produce sodium hydroxide alkali liquid, and purified gypsum is obtained by inducing crystallization, and the leaching agent and electrolyte products are recycled.

Benefits of technology

The high purity (over 98%) and high whiteness (over 94%) of phosphogypsum are achieved, which reduces the consumption and treatment costs of agents, and improves resource utilization by electrolysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430260A_ABST
    Figure CN119430260A_ABST
Patent Text Reader

Abstract

The invention discloses a method for purifying ardealite, and belongs to the technical field of ardealite treatment. The method comprises the following steps: leaching phosphogypsum by adopting a leaching agent, adding a fluorine removal agent, then carrying out solid-liquid separation to obtain a leaching solution and tailings, then adopting a double-chamber diaphragm electrolysis method, taking the leaching solution as an anolyte, taking pure water as a catholyte, and adopting a diaphragm which only allows sodium ions to pass through between a cathode chamber and the anode chamber for blocking, the cathode and the anode jointly form an electrochemical reaction system, an electrolytic reaction is carried out after electrification, hydrogen and oxygen generated by the cathode and the anode are collected respectively, when the pH value of the cathode is increased, sodium ions are diffused to the cathode through the diaphragm and the pH value of the anode is reduced and the pH value is 0.1, seed crystals are added into anolyte for induced crystallization, and filtrate and purified gypsum are obtained through filtration; and the filtrate and the cathode chamber alkali liquor are mixed and then circularly leached to obtain the phosphogypsum. According to the method disclosed by the invention, the impurities in the phosphogypsum can be effectively removed, and the gypsum with low fluorine content, high purity and high whiteness is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of phosphogypsum processing, and in particular to a method for purifying phosphogypsum. Background Art

[0002] Phosphogypsum is a by-product of the wet-process phosphoric acid production process. Its output is extremely large. Every ton of phosphoric acid produced will produce about 4 to 5 tons of phosphogypsum. Phosphogypsum contains residual phosphoric acid, sulfuric acid, hydrofluoric acid, and organic matter, magnesium, aluminum, silicon and other impurities. These impurities will reduce the purity of phosphogypsum and affect the performance of phosphogypsum products. For example, phosphorus and fluorine impurities will affect the setting time of phosphogypsum products and reduce the hardening strength. Silicon impurities are not conducive to the pyrolysis process of phosphogypsum and affect the quality of cement clinker. The presence of organic matter affects the whiteness and strength of phosphogypsum products. These factors restrict the resource utilization and large-scale utilization of phosphogypsum. Therefore, it is very necessary to develop phosphogypsum purification and whitening technology to remove organic matter, silicon, fluorine and other impurities to reduce the adverse factors of its subsequent use.

[0003] At present, the technologies for purifying and whitening phosphogypsum include flotation, calcination and chemical methods. Although the flotation method can remove most of the silicon and organic matter, the purity can reach 95%, and the whiteness can reach up to 70%, there are still a small number of black impurities, which are difficult to remove by flotation, and the whiteness is difficult to further improve. The calcination method can remove organic matter and fluorine, and the whiteness and purity are improved, but silicon is difficult to remove, which affects the application of subsequent products. The chemical method can obtain phosphogypsum with high purity and high whiteness. For example, in patent CN115323476A, ethylenediaminetetraacetic acid salt is used to leaching and calcine phosphogypsum, and the insoluble impurities in the phosphogypsum are removed by solid-liquid separation, and then purified gypsum is obtained by adding sulfuric acid. The purified gypsum obtained has high purity and high whiteness. However, although the calcined gypsum used in this method can remove impurities such as organic matter and fluorine, it increases the processing cost. In addition, a large amount of sulfuric acid is consumed in the purification process, and alkali is consumed in the leaching agent regeneration process. If raw gypsum is used, the leaching method will bring soluble phosphorus and fluorine into the leaching solution, which will enter the product during recrystallization. As the number of leaching agent cycles increases, the soluble phosphorus and fluorine in the leaching solution will also increase. The leaching solution is not suitable for using conventional calcium salts to remove phosphorus and fluorine, because calcium salts will consume the leaching agent, resulting in a decrease in the calcium leaching rate in the phosphogypsum.

[0004] The chemical treatment of phosphogypsum can provide high-quality raw materials for the high-value utilization of phosphogypsum and create greater economic benefits. The chemical treatment method is very promising. However, it is rarely used in industry due to its soluble phosphorus and fluorine impurities affecting product quality, large consumption of treatment agents, and high cost. Therefore, it is urgent to develop efficient impurity removal agents and low-consumption, circular and sustainable chemical purification processes to produce high-purity, high-whiteness purified gypsum while reducing treatment costs. Summary of the invention

[0005] The object of the present invention is to provide a method for purifying phosphogypsum. The method for purifying phosphogypsum provided by the present invention can obtain purified gypsum with high purity and high whiteness, realize the effective removal of impurities in phosphogypsum, and provide high-quality raw materials for the high-value utilization of phosphogypsum. In addition, the method has low reagent consumption and can be recycled. To achieve the above purpose, the technical scheme adopted by the present invention is as follows: (1) Leaching phosphogypsum with an extractant, adding a fluorine-fixing agent and stirring for 30 to 60 minutes, and then separating the solid and liquid to obtain a leachate and tailings; (2) adopting a double-chamber diaphragm electrolysis method, the leaching solution obtained in step (1) is used as the anolyte, pure water is used as the catholyte, the cathode chamber and the anode chamber are separated by a diaphragm, the cathode and the anode together constitute an electrochemical reaction system, and an electrolysis reaction is carried out after power is turned on, the hydrogen and oxygen generated by the cathode and the anode are collected respectively, the pH value of the cathode increases, the sodium ions diffuse to the cathode through the diaphragm, and the cathode chamber obtains a sodium hydroxide alkali solution; (3) When the pH value of the anode drops to 0.1, the anode liquid is taken out and seed crystals are added to induce crystallization at 70-80°C, and the filtrate and purified gypsum are obtained by hot filtration; (4) The filtrate after the reaction in step (3) is mixed with the alkaline solution in the cathode chamber in step (2) and then circulated to extract phosphogypsum.

[0006] Preferably, the leaching agent in step (1) is sodium salts corresponding to formic acid, acetic acid, lactic acid, gluconic acid and their derivatives, the dosage is 2 to 5 times the mass of phosphogypsum, the concentration of phosphogypsum slurry is 8% to 15%, the leaching temperature is 30 to 50°C, and the leaching time is 0.5 to 1h.

[0007] The defluoridation agent is prepared by mixing 20-30 parts of polyacrylamide quaternary ammonium salt, 40-50 parts of polysilicate aluminum iron, 10-20 parts of starch, 1-5 parts of iron-manganese bimetallic oxide, and 5-10 parts of aluminum acrylate coupling agent; The dosage of defluoridation agent is 1‰~5‰ of phosphogypsum.

[0008] The iron-manganese bimetallic oxide is prepared by co-precipitating an iron sulfate solution and a manganese acetate solution in a sodium carbonate solution, filtering, washing, drying, and then calcining at 550-650° C. for 1-2 hours.

[0009] Preferably, in step (2), both the cathode and the anode are inert electrodes, such as platinum electrodes or graphite electrodes, and the cathode chamber and the anode chamber are separated by a diaphragm that only allows sodium ions to pass through.

[0010] Preferably, in step (3), the amount of seed crystals added to the anode liquid is 3-5% of the phosphogypsum, and the induction crystallization time is 1-2 hours.

[0011] Compared with the prior art, the method for purifying phosphogypsum of the present invention has the following beneficial effects: (1) The homemade defluoridation agent of the present invention can effectively reduce the fluorine content in the leachate, and the total fluorine content of the purified gypsum is less than 30 mg / kg. The defluoridation agent will not consume the leaching agent and will not affect the leaching of calcium in the phosphogypsum.

[0012] (2) The present invention adopts a coupled process of leaching and electrolysis, which can effectively improve the purity and whiteness of phosphogypsum. The purity of the purified gypsum is above 98%, and the whiteness is above 94%. In addition, hydrogen and oxygen can be produced as by-products. The leaching agent can be recycled, thereby improving the utilization rate of raw materials and reducing production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0014] Example 1 (1) Leach phosphogypsum with sodium gluconate, the dosage is 3 times the mass of phosphogypsum, the concentration of phosphogypsum slurry is 10%, the dosage of defluoridation agent is 1‰ of phosphogypsum, the leaching temperature is 30℃, and the leaching time is 0.5h; The defluoridating agent is prepared by mixing 30 parts of polyacrylamide quaternary ammonium salt, 40 parts of polyaluminum ferrosilicate, 10 parts of starch, 5 parts of iron-manganese bimetallic oxide, and 5 parts of aluminum acrylate coupling agent, wherein the iron-manganese bimetallic oxide is co-precipitated with 1M ferric sulfate solution and 1.5M manganese acetate solution using 0.5M sodium carbonate solution, and the obtained product is washed, dried, and then calcined at 550°C for 2 hours.

[0015] (2) adopting a double-chamber diaphragm electrolysis method, the leaching solution obtained in step (1) is used as the anolyte, pure water is used as the catholyte, the cathode chamber and the anode chamber are separated by a diaphragm, the cathode and the anode together constitute an electrochemical reaction system, and an electrolysis reaction is carried out after power is turned on, the hydrogen and oxygen generated by the cathode and the anode are collected respectively, the pH value of the cathode increases, the sodium ions diffuse to the cathode through the diaphragm, and the cathode chamber obtains a sodium hydroxide alkali solution; (3) When the pH value of the anode drops to 0.1, the anode liquid is taken out and seed crystals are added. The amount of seed crystals added is 5% of the phosphogypsum. Induced crystallization is carried out at 80°C for 1 hour. The filtrate and purified gypsum are obtained by hot filtration. The purified gypsum obtained by this method has a purity of 99.1%, a whiteness of 94.2%, a yield of 95.5%, and a total fluorine content of 25.6 mg / kg.

[0016] Example 2 The operation steps are the same as those in Example 1, except that sodium lactate is used for leaching in step (1), the amount used is 4 times the mass of the phosphogypsum, the concentration of the phosphogypsum slurry is 15%, the amount of the defluoridating agent is 2‰, the leaching temperature is 50°C, and the leaching time is 1 h; In step (3), the amount of seed crystal added is 4% of the phosphogypsum, and the induced crystallization is carried out at 80° C. The reaction time is 1.5 h.

[0017] The purified gypsum obtained by this method has a purity of 98.5%, a whiteness of 94.1%, a yield of 94.7%, and a total fluorine content of 19.8 mg / kg.

[0018] Example 3 The operation steps are the same as those in Example 1, except that sodium acetate is used for leaching in step (1), the amount used is 4.5 times the mass of the phosphogypsum, the concentration of the phosphogypsum slurry is 10%, the amount of the defluorinating agent is 2.5‰, the leaching temperature is 35°C, and the leaching time is 0.7h; In step (3), the amount of seed crystal added is 4.5% of the phosphogypsum, and the induced crystallization is carried out at 70° C. The reaction time is 1 h.

[0019] The purified gypsum obtained by this method has a purity of 99.1%, a whiteness of 94.3%, a yield of 93.2%, and a total fluorine content of 20.4 mg / kg.

[0020] Example 4 The operation steps are the same as those in Example 1, except that sodium formate is used for leaching in step (1), the amount used is 5 times the mass of the phosphogypsum, the concentration of the phosphogypsum slurry is 12%, the amount of the defluorinating agent is 4‰, the leaching temperature is 30°C, and the leaching time is 0.7h; In step (3), the amount of seed crystal added is 4.5% of the phosphogypsum, and the induced crystallization is carried out at 70°C for 2 hours.

[0021] The purified gypsum obtained by this method has a purity of 99.1%, a whiteness of 94.3%, a yield of 92.7%, and a total fluorine content of 15.8 mg / kg.

[0022] Example 5 The operation steps are the same as those in Example 1, except that sodium lactate is used for leaching in step (1), the amount used is 5 times the mass of the phosphogypsum, the concentration of the phosphogypsum slurry is 12%, the amount of the defluoridating agent is 5‰, the leaching temperature is 45°C, and the leaching time is 1 h; In step (3), the amount of seed crystal added is 5% of the phosphogypsum, and the induced crystallization is carried out at 80°C for 1.5 hours.

[0023] The purified gypsum obtained by this method has a purity of 98.3%, a whiteness of 93.9%, a yield of 93.7%, and a total fluorine content of 14.2 mg / kg.

[0024] Comparative Example 1 The operation steps are the same as those in Example 1, except that no defluorinating agent is added.

[0025] The purified gypsum obtained by this method has a purity of 98.2%, a whiteness of 94.1%, and a total fluorine content of 150.6 mg / kg.

[0026] Comparative Example 2 Step 1 is the same as in Example 1, except that the pH is adjusted to 0.1 by adding sulfuric acid instead of electrolysis, and then the same as in Step 3 in Example 1 is performed.

[0027] The purified gypsum obtained by this method has a purity of 99.4%, a whiteness of 94.1%, a yield of 95.5%, and a total fluorine content of 26.6 mg / kg.

[0028] The purity of the purified gypsum in Examples 1-5 is all above 98%, the whiteness is all above 94%, the yield is all above 90%, and the total fluorine content is all below 30 mg / kg. Compared with Comparative Example 1, the purity of the purified gypsum obtained without the addition of the fluorine agent in Example 1 is lower and the total fluorine content is higher, which indicates that the defluorinating agent can effectively fix the fluorine in the phosphogypsum, and less fluorine enters the leaching solution. The homemade defluorinating agent can combine with the fluorine in the leachate to form a complex precipitate that enters the tailings, thereby reducing the fluorine content in the leachate and the total fluorine content of the product. Compared with Example 1 and Comparative Example 1, recrystallization can be achieved by adding acid without electrolysis, and the purity and whiteness of the purified gypsum obtained are both high, and the total fluorine content is low. The yield of adding sulfuric acid is slightly higher. This may be that the sulfate in sulfuric acid promotes the crystallization of calcium sulfate dihydrate, but the acid addition method also needs to consider the recovery of excess acid and the regeneration of solvent, and the consumption of alkali is required. The electrolysis method better solves the problem of solvent recovery and reuse, and the hydrogen and oxygen generated during electrolysis can be used after being collected separately. The pH of the electrolysis anolyte is reduced and calcium sulfate crystals will not precipitate, and will not affect the work of the electrode. This is because the leaching agent and calcium have a strong binding ability, and the reduction of acidity will not destroy the binding between the leaching agent and calcium, but by heating, the binding ability between calcium and the leaching agent decreases, and calcium and sulfate are recombined to form calcium sulfate crystals. The above embodiments and comparative examples show that the method can obtain gypsum with high purity, high whiteness and low fluorine content, providing high-quality raw materials for the high-value utilization of phosphogypsum, and the method can be recycled, with low energy consumption and low cost.

[0029] The above description is only a preferred embodiment of the present invention, and is not intended to limit the implementation scheme. It should be noted that it is possible for a person skilled in the art to make several improvements and changes without departing from the creative concept of the present invention, and these all fall within the scope of protection of the present invention.

Claims

1. A method for purifying phosphogypsum, comprising the following steps: (1) Leaching phosphogypsum with an extractant, adding a defluorinating agent and stirring for 30 to 60 minutes, and then separating the solid and liquid to obtain a leachate and tailings; (2) adopting a double-chamber diaphragm electrolysis method, using the leaching solution obtained in step (1) as the anolyte, pure water as the catholyte, the cathode chamber and the anode chamber are separated by a diaphragm, the cathode and the anode together constitute an electrochemical reaction system, and an electrolysis reaction is carried out after power is turned on, and the hydrogen and oxygen generated by the cathode and the anode are collected respectively, the pH value of the cathode increases, and the sodium ions diffuse to the cathode through the diaphragm, and the cathode chamber obtains sodium hydroxide alkali solution; (3) When the pH value of the anode drops to 0.1, the anode liquid is taken out and seed crystals are added to induce crystallization at 70-80°C, and the filtrate and purified gypsum are obtained by hot filtration; (4) The filtrate after the reaction in step (3) is mixed with the alkaline solution in the cathode chamber in step (2) and then circulated to extract phosphogypsum.

2. The processing method according to claim 1, characterized in that: In the step (1), the leaching agent is sodium salts corresponding to formic acid, acetic acid, lactic acid, gluconic acid and their derivatives, the dosage is 2 to 5 times the mass of phosphogypsum, the concentration of phosphogypsum slurry is 8% to 15%, the leaching temperature is 30 to 50°C, and the leaching time is 0.5 to 1h.

3. The processing method according to claim 1, characterized in that: In step (1), the defluorination agent is prepared by mixing 20-30 parts of polyacrylamide quaternary ammonium salt, 40-50 parts of polyaluminum ferrosilicate, 10-20 parts of starch, 1-5 parts of iron-manganese bimetallic oxide, and 5-10 parts of aluminum acrylate coupling agent; The dosage of defluoridation agent is 1‰~5‰ of phosphogypsum.

4. The processing method according to claim 3, characterized in that: The iron-manganese bimetallic oxide is prepared by co-precipitating an iron sulfate solution and a manganese acetate solution in a sodium carbonate solution, filtering, washing, drying, and then calcining at 550-650° C. for 1-2 hours.

5. The processing method according to claim 1, characterized in that: In step (2), both the cathode and the anode are inert electrodes, such as platinum electrodes or graphite electrodes, and the cathode chamber and the anode chamber are separated by a diaphragm that only allows sodium ions to pass through.

6. The processing method according to claim 1, characterized in that: In the step (3), the amount of seed crystals added to the anode liquid is 3-5% of the phosphogypsum, and the induction crystallization time is 1-2 hours.